USE MODERN METHODS OF TEACHING FOREIGN LANGUAGE - Utaev Shukhratjon Shavkatovich (Galaxy International Interdisciplinary Research Journal, 2022)
Known to be a constructivist approach, modern teaching differs from traditional teaching methods. Students aren't instructed to memorize and recite. Instead, modern teaching methods emphasize that learning objectives be met through classroom interaction, collaboration and active participation in engaging activities